The Local Order and Structural Study of Liquid PdAg Alloy during Cooling Processes under Different Pressures - Kazanc, Sefa; Celik, Fatih Ahmet (Elsevier, 2014)
The pressure effect on the rapid solidification of a liquid PdAg alloy system is studied by using the molecular dynamics (MD) simulation method. The physical interactions between the atoms in the model alloy systems were modeled using the Sutton-Chen version of the embedded atom method. Crystal and amorphous phase transitions for different pressures were formed at cooling rates of 2 x 10(11), 2 x 10(12), and 2 x 10(13) K/s, respectively. The temperatures of crystallization formation at slow cooling rate and the icosahedral order in the amorphous phase at high cooling rate are determined by using a radial distribution function, Wendt-Abraham parameters, and a bond orientational order parameter under different pressures. It is observed that an increase of pressure causes an increase of the crystal and glass formation temperatures.
Keywords: Embedded-Atom Method; Computer-Simulation; Molecular-Dynamics; Supercooled Liquid